The perceived impact of social media advertising on the online purchasing intention of Telecommunication Consumers in Gauteng - Joseph, Brogan Kairo (The IIE, 2020)
With the digital age vastly progressing, many companies including the South African telecommunications company ‘Rain’ are utilising social media platforms such as Facebook and Instagram to advertise their products and services to obtain a greater target market and profit. The aim of this study understands the extent to how ‘Rain’ social media advertisements influence its consumers intention to purchase its products online. The study used the theory of planned behaviour to understand how consumers interpret and process the information in ‘Rains’ social media advertisements to understand the perceived impact it has on the consumers purchasing intention. Semi-structured interviews were conducted online with five participants (all of whom are Rain consumers). The responses were analysed using thematic analysis whereby six key themes were identified. It was found that other factors added to the perceived influences of online purchasing intention such as word-of-mouth and online safety and television advertisements seem to have a greater influence on the consumers purchasing intention than social media advertisements, differing from the previous literature. The results suggest that Rain’s social media advertisements is not a perceived influence of consumers online purchasing decisions as other forms of communication outweigh social media advertising.
Keywords: Perceptions; Social media; Advertising; Telecommunication consumers; Online shopping; Purchasing intention